Temporal variation in ecological and evolutionary contributions to phytoplankton functional shifts. Issue 2 (23rd November 2022) - Hattich, Giannina S. I.; Listmann, Luisa; Havenhand, Jonathan; Reusch, Thorsten B. H.; Matthiessen, Birte
Abstract: Communities and their functioning are jointly shaped by ecological and evolutionary processes that manifest in diversity shifts of their component species and genotypes. How both processes contribute to community functional change over time is rarely studied. We here repeatedly quantified eco‐evolutionary contributions to CO2 ‐driven total abundance and mean cell size changes after short‐, mid‐, and longer‐term (80, 168, and > 168 d, respectively) in experimental phytoplankton communities. While the CO2 ‐driven changes in total abundance and mean size in the short‐ and mid‐term could be predominantly attributed to ecological shifts, the relative contribution of evolution increased. Over the longer‐term, the CO2 ‐effect and underlying eco‐evolutionary changes disappeared, while total abundance increased, and mean size decreased significantly independently of CO2 . The latter could be presumably attributed to CO2 ‐independent genotype selection which fed back to species composition. In conclusion, ecological changes largely dominated the regulation of environmentally driven phytoplankton functional shifts at first. However, evolutionary changes gained importance with time, and can ultimately feedback on species composition, and thus must be considered when predicting phytoplankton change.